The Archaeology of Race : The Eugenic Ideas of Francis Galton and Flinders Petrie - Challis, Debbie (Criminal Practice Ser, 2013)
Title page -- Contents -- Figures -- Abbreviations -- Foreword by Natasha McEnroe -- Acknowledgements -- Introduction -- 1 Races and Men: 'All Is Race' -- Robert Knox: Biographical sketch -- Knox: The lecturer and lectures -- Knox and Egypt -- Legacy and racial theory -- 2 Galton and Genius -- Race relations in the 1860s -- Inherent genius -- Muscling in -- Sport and race -- 3 Fitting Aesthetics -- Face of the past -- The chosen inch -- Defining eugenics -- 4 Photographing Races from Antiquity -- Scientific support -- Logistics and money -- The journey -- Back home -- 5 Greek Art, Greek Faces? -- Found and exhibited -- Greek in face -- From face to place -- Reconstructing faces -- 6 Peopling the Old Testament -- The 'Perfect Composite' -- Putting faces to the Bible -- Faces of Israel and Egypt -- 7 Akhenaten's Bloodline -- Akhenaten and the Bible -- The face of Akhenaten -- Archaeological fantasy -- Trading race -- Queen Tiye and empowerment -- 8 The New Ancient Race -- Naqada I -- Measuring skulls -- Ipswich 1895 -- Galton in Egypt -- 9 Flinders Petrie and Edwardian Politics -- Edwardian eugenics -- 10 Heads -- Greek and Egyptian Memphis -- Petrie's 'Race' heads -- The head of William Matthew Flinders Petrie -- Afterword by Kate Sheppard -- Appendix: Heads from Memphis and their Racial Types -- Bibliography -- Index -- Copyright.